Stabilization of durable tetragonal phase and barrier regions in y-123 ceramic systems with partial substitution mechanism - Güdücü, Gülnur; Safran, Serap; Kurnaz, Sedat; Tokeşer, Elif Aşikuzun; Seydioğlu, Turgay; Yildirim, Gürcan; Öztürk, Özgür (Springer Science and Business Media LLC, 2024)
AbstractThis study examines the impact of Tb and Zn doping on the Y-123 superconducting system by analyzing crack propagation mechanisms through Vickers microhardness measurements. The measurements are conducted at various application forces ranging from 0.245 N to 2.940 N. The microhardness measurements are used to determine the role of impurity addition on Vickers hardness, modulus of elasticity, brittleness index, fracture toughness, and yield strengths. It is found that impurity ions serving as strong barrier regions improve the surface residual compressive stress sites and interactivity between the adjacent layers. Similarly, the sensitivity to the external forces reduce significantly with the substitution mechanism due to the induced new slip systems and ionic bond formations. Accordingly, all the mechanical performance properties are recorded to increase significantly with the impurity ions. Especially, the replacement of Zn by Cu ions in the Y-123 matrix exhibits higher resistance to failure, mechanical strength, and stabilization of the durable tetragonal phase. Accordingly, Zn/Cu substitution in Y-123 ceramics paves the way for the applications of ceramic compounds in the fields of heavy-industrial technology and industrial power systems. All the ceramic materials also exhibit indentation size effect feature based on the recovery mechanism. Additionally, load-independent microhardness parameters are semi-empirically modeled by Meyer's law, Hays-Kendall, indentation-induced cracking, elastic–plastic deformation, and proportional sample resistance model for the first time. According to the comparisons, the IIC model is identified as the most suitable for interpreting the real microhardness results of newly produced Y-123 ceramic matrices.
Keywords: Superconducting System; Microhardness; Fracture Toughness; Indentation-Induced Cracking; Various Application; Recovery Mechanism